Interleukin‐2 critically regulates bone marrow erythropoiesis and prevents anemia development. Issue 12 (15th October 2015) - Chopra, Martin; Langenhorst, Daniela; Beilhack, Andreas; Serfling, Edgar; Patra, Amiya K.
Abstract : Mice deficient in IL‐2 signaling develop severe anemia indicating a defect in erythropoiesis. However, why deficiency in IL‐2, an essential growth factor for lymphocytes, or in IL‐2 signaling components should result in defective erythropoiesis is unclear. Here, we have analyzed the mechanism of IL‐2 signaling deficiency induced anemia in mice and show that IL‐2 plays an indispensable role in bone marrow (BM) erythropoiesis via maintenance of regulatory T (Treg) cells. In absence of IL‐2 signaling, IFN‐γ produced by the activated T cells suppressed klf1 expression, resulting in an early block in erythrocyte differentiation. Anemia, in IL‐2 or IL‐2 signaling deficient mice always developed prior to the manifestation of other autoimmune complications such as colitis, suggesting that anemia in these mice might be a contributing factor in inducing other pathological complications in later stages. Our study shows, how essential cytokines of lymphoid cells could exert critical influence on the development of erythrocytes and thus expanding our understanding of the complex regulation of hematopoiesis in the BM. Besides, our findings might facilitate the use of IL‐2 and anti‐IFN‐γ as a clinical remedy against anemia that arise in cancer patients following radiotherapy or chemotherapy, a context which simulates the situation of IL‐2 deficiency.